The Evaluation of Antibiotics Using to Pediatric Acute Upper Respiratory Tract Infection Patients at Health Centers in Kunduran Blora 2013 - Tesar Zulmi Antoro; Nurul Mutmainah (Universitas Muhammadiyah Surakarta, 2017)
Acute respiratory tract infection is an acute infection which attacks one or more part of respiratory tractfrom nose to alveoli. This disease is an important society’s health problem especially in the developingcountries which attacks children easily especially who have low body’s immunity. This aim of the researchwas to know representation of the treatment and the accuracy of antibiotics distribution as the treatment ofpediatric patients of acute upper respiratory tract infection (AURTI) at Health Center in Kunduran, Blora2013 which is observed by appropriate parameter indication, appropriate drugs, appropriate dose andappropriate patients using the standard from WHO (2003). This research was categorized as qualitativeand non experimental research. In obtaining the data, the researcher trace the pediatric patient’s medicalrecord in the registration book in the health center Kunduran, Blora regency year 2013. The obtained datawas analyzed descriptively to evaluate the rationality of antibiotics distribution for AURTI. The researchresult showed that over 110 of the available samples in children aged up to 12 years old which werediagnosed as AURTI sufferer, 92 cases (83.63%) used amoxicillin antibiotics, 18 cases (16.37%) usedkotrimoksazol, 72 cases (65.50%) were proper indication, 59 case (53.63%) were proper drugs, 110 cases(100%) were proper patients, 87 case (79.09%) were proper dose, and 47 case (42.70) were rational in thetreatment